The mind incarnate - Shapiro, Lawrence A. (Life and mind., 2004)
"How are the mind and body harnessed together? In The Mind Incarnate Lawrence Shapiro addresses this question by testing two widely accepted hypothesis, the multiple realizability thesis and the separability thesis. He argues that there is significant - though far from decisive - evidence against them."